Role of type 2 innate lymphoid cell and its related cytokines in tumor immunity. Issue 4 (17th October 2019) - Wan, Jie; Cai, Wei; Wang, Huixuan; Cheng, Jianjun; Su, Zhaoliang; Wang, Shengjun; Xu, Huaxi
Abstract: Type 2 innate lymphoid cells (ILC2s) have multiple functions that can respond to allergic diseases, parasite infection, metabolic homeostasis, tissue repair, and adipose metabolism homeostasis. In these diseases, ILC2s can be activated by various inflammatory cytokines released by damaged cells. Activated ILC2s produce different type 2 cytokines, including interleukin (IL)‐4, IL‐5, IL‐9, and IL‐13, which involved in the pathogenesis of many diseases. In recent years, the relationship between ILC2s and tumor diseases has attracted more and more attention. The role of ILC2s in tumor immunity depends on its surface molecules and cytokine context. This review aims to conclude tumorigenic and antitumorigenic roles of ILC2s, and the characters of ILC2s‐related cytokines in tumor diseases to provide a comprehensive overview of the impact of ILC2s in tumor immunity. Abstract : This review aims to conclude tumorigenic and antitumorigenic roles of type 2 innate lymphoid cells (ILC2s), and the characters of ILC2s‐related cytokines in tumor diseases.